2011
DOI: 10.1007/s13204-011-0027-y
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis and catalytic studies of CdS–manganese oxide nanocomposite

Abstract: Cadmium sulfide (CdS)-manganese oxide (MO) nanocomposite was synthesized by the ion exchange and ultrasonic irradiation methods. The synthesized nanocomposite was characterized by FTIR, powder X-ray diffractrogram (XRD), UV-Vis diffused reflectance spectra (UVDRS), photoluminescence (PL), transmission electron microscope (TEM) and energy dispersive X-ray analysis (EDX). The experimental results confirm the formation of CdS-MO nanocomposite. The luminescence of the nanocomposite exhibits a notable blue shift. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The characteristic peaks of silica appeared at 1089.02 cm −1 and 779.85 cm −1 , and the high intensity absorption peaks at 799.02 cm −1 were caused by the symmetric stretching vibration of Si-O-Si [31]. The peaks at 694.97 cm −1 , 518.41 cm −1 , and 464.43 cm −1 were determined to be the characteristic peaks of manganese oxide [32], while the peaks at 1163.86 cm −1 represented the vibration absorption peaks of MnOOH of molybdenite [33]. The peak at 914.47 cm −1 was attributed to the stretching vibration absorption peak of Al-OH [34].…”
Section: Study On the Combined Remediation Mechanismmentioning
confidence: 99%
“…The characteristic peaks of silica appeared at 1089.02 cm −1 and 779.85 cm −1 , and the high intensity absorption peaks at 799.02 cm −1 were caused by the symmetric stretching vibration of Si-O-Si [31]. The peaks at 694.97 cm −1 , 518.41 cm −1 , and 464.43 cm −1 were determined to be the characteristic peaks of manganese oxide [32], while the peaks at 1163.86 cm −1 represented the vibration absorption peaks of MnOOH of molybdenite [33]. The peak at 914.47 cm −1 was attributed to the stretching vibration absorption peak of Al-OH [34].…”
Section: Study On the Combined Remediation Mechanismmentioning
confidence: 99%
“…The peak near 1600 cm −1 in the fresh catalyst (Figure 2(a)) was assigned to the bending vibration of water and OH, which suggests that hydroxyl group is present in the prepared catalyst. The spectra of used catalysts (Figure 2(b) and (c)) show bands at 1592 cm −1 , which may be due to MnH 2 with H derived from benzyl alcohol [14][15][16][17][18][19][20][21].…”
Section: Xrd Analysismentioning
confidence: 99%
“…through positive holes [9]. Kannan et al demonstrated decolorization of "methylene blue" and "amido black" dyes with layered-and octahedral manganese oxides in the presence of hydrogen peroxide [10]. Ultrasonic radiation was found to enhance the activity of MnO 2 catalyst in the degradation of "acid red B" [11].…”
Section: Introductionmentioning
confidence: 99%